Group ib element-doped n-type bismuth telluride thermoelectric material, and preparation method and application thereof
Patent Information
- Application Number
- CN202611048124.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-15
- Publication Date
- 2026-10-13
AI Technical Summary
本发明从同族元素调控角度出发,通过IB族元素掺杂调控Bi2Te2.7Se0.3晶体材料,形成Bi2Te2.7Se0.3Mx晶体材料,从而提高其载流子迁移率和功率因子,实现室温区热电性能的提升,将IB族元素掺杂的n型碲化铋基热电材料与p型碲化铋基热电材料Bi0.48Sb1.52Te3.06配合使用,构成七对近室温全尺寸热电制冷模块,在303K、323K、343K下分别实现了64.8K、73.87K和81.95K的制冷温差,∆T =5K,I=1A的条件下,该模块的最大COP达到3.4,结果表明本发明的n型Bi2Te2.7Se0.3Mx晶体材料在热电和制冷领域有稳定的表现。
Smart Images

Figure CN122897369A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of thermoelectric materials and semiconductor refrigeration technology, specifically relating to an n-type bismuth telluride thermoelectric material doped with group IB elements, its preparation method, and its application. Background Technology
[0002] Thermoelectric materials enable the direct conversion between thermal energy and electrical energy, offering advantages such as solid-state operation, no moving mechanical parts, high reliability, and ease of miniaturization and integration. They can be used in waste heat recovery, thermoelectric power generation, and semiconductor refrigeration. Near-room temperature thermoelectric refrigeration devices have significant application value in scenarios such as heat dissipation for electronic devices, precision temperature control, and portable refrigeration.
[0003] Bi₂Te₃-based materials are among the most widely used thermoelectric material systems in the near-room temperature range. Compared with p-type Bi₂Te₃-based materials, n-type Bi₂Te₃-based materials still have room for improvement in terms of carrier concentration, mobility, defect control, and thermal conductivity optimization. The key to improving the near-room temperature thermoelectric performance of n-type Bi₂Te₃-based materials lies in optimizing both electrical and thermal transport without significantly disrupting the crystal structure. Summary of the Invention
[0004] The technical problem to be solved by this invention is to address the shortcomings of the prior art by providing an n-type bismuth telluride thermoelectric material doped with group IB elements, its preparation method, and its application, thereby regulating Bi2Te through group IB element doping. 2.7 Se 0.3 Crystalline materials can be used to improve carrier mobility and power factor, thereby enhancing thermoelectric performance in the room temperature range.
[0005] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is: an n-type bismuth telluride thermoelectric material doped with group IB elements, characterized in that the n-type bismuth telluride thermoelectric material doped with group IB elements is a crystalline material with the general chemical formula Bi₂Te. 2.7 Se 0.3 M x , where M represents a group IB element, selected from Cu or Ag; When M is Cu, the value of x is: 0.0025≤x≤0.010; When M is Ag, the value of x is: 0.005≤x≤0.01.
[0006] This invention also provides a method for preparing the above-mentioned n-type bismuth telluride thermoelectric material doped with Group IB elements, the method being: Step 1: Use Bi, Te, Se and M with a purity of not less than 99.5% as raw materials, and mix them in a molar ratio of Bi, Te, Se and M of 2:2.7:0.3:x to obtain mixed raw materials; Step 2: Place the mixed raw materials obtained in Step 1 into a quartz tube and perform high-temperature melting to synthesize a compound; Step 3: The compound synthesized in Step 2 is subjected to slow cooling crystal growth to obtain n-type bismuth telluride thermoelectric material doped with group IB elements.
[0007] Preferably, in step two, the mixed raw materials are placed in a quartz tube and subjected to vacuum treatment, with a vacuum degree of less than 1×10⁻⁶. - 3 Pa, the vacuum-sealed quartz tube is vertically placed in a high-temperature box-type muffle furnace for high-temperature melting and synthesis reaction; the quartz tube is a bottom-conical quartz tube with a wall thickness of not less than 1 mm, and the angle θ of the bottom cone of the quartz tube is in the range of 15°≤θ / 2≤25°.
[0008] Preferably, the high-temperature melting synthesis reaction in step two specifically involves: first, placing a quartz tube containing the mixed raw materials into a high-temperature box-type muffle furnace, controlling the high-temperature box-type muffle furnace to heat up to 800°C at a rate of 60~70°C / h, and holding it at that temperature for 700~750 min.
[0009] Preferably, the cooling growth described in step three specifically involves: The temperature of the high-temperature box-type muffle furnace was reduced to 520-570℃ at a rate of 1.5-2℃ / h and held for 1400-1500 min for slow cooling crystal growth; then the furnace was naturally cooled to 20-30℃ to obtain n-type bismuth telluride thermoelectric material doped with group IB elements.
[0010] The present invention also provides a thermoelectric cooling device, wherein the thermoelectric cooling device comprises the n-type bismuth telluride-based thermoelectric material doped with group IB elements.
[0011] Preferably, the n-type bismuth telluride-based thermoelectric material doped with group IB elements and the p-type bismuth telluride-based thermoelectric material Bi 0.48 Sb 1.52 Te 3.06 When used together, they form seven pairs of near-room temperature full-size thermoelectric refrigeration modules.
[0012] Compared with the prior art, the present invention has the following advantages: This invention focuses on the regulation of Bi2Te by doping with group IB elements. 2.7 Se 0.3 Crystalline material, forming Bi2Te 2.7 Se 0.3 M x Crystal materials, thereby improving their carrier mobility and power factor, and achieving enhanced thermoelectric performance in the room temperature range, are combined with n-type bismuth telluride-based thermoelectric materials doped with group IB elements and p-type bismuth telluride-based thermoelectric materials. 0.48Sb 1.52 Te 3.06 When used together, seven pairs of near-room-temperature full-size thermoelectric cooling modules were constructed. Cooling temperature differences of 64.8K, 73.87K, and 81.95K were achieved at 303K, 323K, and 343K, respectively. Under the conditions of ∆T = 5K and I = 1A, the maximum COP of this module reached 3.4. The results indicate that the n-type Bi₂Te of this invention… 2.7 Se 0.3 M x Crystalline materials exhibit stable performance in thermoelectric and refrigeration applications.
[0013] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0014] Figure 1 Conductivity test diagrams of n-type Bi2Te2.7Se0.3 crystal materials doped with Group IB elements prepared in Examples 1-8 and Comparative Examples 1-7 of this invention; Figure 2 n-type Bi₂Te doped with group IB elements was prepared for Examples 1-8 and Comparative Examples 1-7 of this invention. 2.7 Se 0.3 Seebeck coefficient test diagram of crystalline materials; Figure 3 n-type Bi₂Te doped with group IB elements was prepared for Examples 1-8 and Comparative Examples 1-7 of this invention. 2.7 Se 0.3 Power factor test graph of crystalline materials; Figure 4 n-type Bi₂Te doped with group IB elements was prepared for Examples 1-8 and Comparative Examples 1-7 of this invention. 2.7 Se 0.3 Graph showing the total thermal conductivity of crystalline materials; Figure 5 n-type Bi₂Te doped with group IB elements was prepared for Examples 1-8 and Comparative Examples 1-7 of this invention. 2.7 Se 0.3 ZT value test chart of crystalline materials; Figure 6 n-type Bi₂Te doped with group IB elements prepared in Example 6 of this invention 2.7 Se 0.3 Crystal materials and p-type Bi 0.48 Sb 1.52 Te 3.06 A test diagram of the refrigeration temperature difference of seven pairs of full-size thermoelectric coolers; Figure 7 n-type Bi₂Te doped with group IB elements prepared in Example 6 of this invention 2.7 Se0.3 Crystal materials and p-type Bi 0.48 Sb 1.52 Te 3.06 A graph showing the coefficient of performance (COP) test results of seven pairs of full-size thermoelectric coolers. Detailed Implementation
[0015] I. Preparation of Cu-doped Samples Example 1
[0016] This embodiment discloses a Cu-doped Bi₂Te 2.7 Se 0.3 Crystal materials (Bi2Te) 2.7 Se 0.3 Cu x A method for preparing (x=0.0025), the method comprising the following steps: Step 1: Use high-purity (quality ≥ 99.5%) Bi, Te, Se and Cu particles as initial raw materials, and mix them according to the molar ratio of Bi:Te:Se:Cu = 2:2.7:0.3:0.0025 to obtain mixed raw materials.
[0017] Step 2: Place the mixed raw materials into a quartz tube and perform a vacuum treatment, with a vacuum degree of less than 1×10⁻⁶. - 3 Pa; The quartz tube is a quartz tube with a pointed bottom cone shape, and its wall thickness is not less than 1 mm. The angle θ of the bottom cone of the quartz tube is in the range of θ / 2=25°.
[0018] Step 3: First, raise the temperature of the high-temperature box-type muffle furnace to 800℃ at a rate of 65℃ / h, and maintain this temperature for 740 minutes to carry out the high-temperature melting synthesis reaction.
[0019] Step 4: After the high-temperature melting synthesis reaction is completed, the temperature of the high-temperature box-type muffle furnace is reduced to 550℃ at a rate of 1.8℃ / h, and this temperature is maintained for 1440 min to carry out slow cooling crystal growth.
[0020] Step 5: Naturally cool the high-temperature box-type muffle furnace to 20°C to obtain n-type Bi₂Te that can be used for thermoelectric refrigeration. 2.7 Se 0.3 Cu 0.0025 Crystalline materials.
[0021] In this invention, the angle θ of the bottom cone of the quartz tube can be within the range of 15°≤θ / 2≤25°. In the specific experiment, a quartz tube with a bottom cone angle θ satisfying θ / 2=25° was used.
[0022] Example 2
[0023] This embodiment discloses a Cu-doped Bi₂Te 2.7 Se 0.3 Crystal materials (Bi2Te) 2.7 Se 0.3 Cu x A method for preparing (x=0.0075), the method comprising the following steps: Step 1: Use high-purity Bi, Te, Se and Cu particles as initial raw materials, and mix them according to the molar ratio of Bi:Te:Se:Cu=2:2.7:0.3:0.0075 to obtain mixed raw materials.
[0024] Step 2: Place the mixed raw materials into a quartz tube and perform a vacuum treatment, with a vacuum degree of less than 1×10⁻⁶. - 3 Pa; The quartz tube is a quartz tube with a pointed bottom cone shape, and its wall thickness is not less than 1 mm. The angle θ of the bottom cone of the quartz tube is in the range of θ / 2=25°.
[0025] Step 3: First, raise the temperature of the high-temperature box-type muffle furnace to 800℃ at a rate of 60℃ / h, and maintain this temperature for 750 minutes to carry out the high-temperature melting synthesis reaction.
[0026] Step 4: After the high-temperature melting synthesis reaction, the temperature of the high-temperature box-type muffle furnace is reduced to 520℃ at a cooling rate of 1.5℃ / h, and this temperature is maintained for 1500min to carry out slow cooling crystal growth.
[0027] Step 5: Naturally cool the high-temperature box-type muffle furnace to 20°C to obtain n-type Bi₂Te that can be used for thermoelectric refrigeration. 2.7 Se 0.3 Cu 0.0075 Crystalline materials.
[0028] Example 3
[0029] This embodiment discloses a Cu-doped Bi₂Te 2.7 Se 0.3 Crystal materials (Bi2Te) 2.7 Se 0.3 Cu x A method for preparing (x=0.0075), the method comprising the following steps: Step 1: Use high-purity Bi, Te, Se and Cu particles as initial raw materials, and mix them according to the molar ratio of Bi:Te:Se:Cu=2:2.7:0.3:0.0075 to obtain mixed raw materials.
[0030] Step 2: Place the mixed raw materials into a quartz tube and perform a vacuum treatment, with a vacuum degree of less than 1×10⁻⁶. -3 Pa; The quartz tube is a quartz tube with a pointed bottom cone shape, and its wall thickness is not less than 1 mm. The angle θ of the bottom cone of the quartz tube is in the range of θ / 2=25°.
[0031] Step 3: First, raise the temperature of the high-temperature box-type muffle furnace to 800℃ at a rate of 70℃ / h, and maintain this temperature for 700min to carry out the high-temperature melting synthesis reaction.
[0032] Step 4: After the high-temperature melting synthesis reaction, the temperature of the high-temperature box-type muffle furnace is reduced to 570℃ at a cooling rate of 2℃ / h, and this temperature is maintained for 1400min for slow cooling crystal growth.
[0033] Step 5: Naturally cool the high-temperature box-type muffle furnace to 30°C to obtain n-type Bi₂Te that can be used for thermoelectric refrigeration. 2.7 Se 0.3 Cu 0.0075 Crystalline materials.
[0034] Example 4
[0035] This embodiment discloses a Cu-doped Bi₂Te 2.7 Se 0.3 Crystal materials (Bi2Te) 2.7 Se 0.3 Cu x A method for preparing (x=0.005), the method comprising the following steps: Step 1: Use high-purity Bi, Te, Se and Cu particles as initial raw materials, and mix them according to the molar ratio of Bi:Te:Se:Cu=2:2.7:0.3:0.005 to obtain mixed raw materials.
[0036] Step 2: Place the mixed raw materials into a quartz tube and perform a vacuum treatment, with a vacuum degree of less than 1×10⁻⁶. - 3 Pa; The quartz tube is a quartz tube with a pointed bottom cone shape, and its wall thickness is not less than 1 mm. The angle θ of the bottom cone of the quartz tube is in the range of θ / 2=25°.
[0037] Step 3: First, raise the temperature of the high-temperature box-type muffle furnace to 800℃ at a rate of 60~70℃ / h, and maintain this temperature for 740 minutes to carry out the high-temperature melting synthesis reaction.
[0038] Step 4: After the high-temperature melting synthesis reaction, the temperature of the high-temperature box-type muffle furnace is reduced to 550℃ at a cooling rate of 1.5~2℃ / h, and this temperature is maintained for 1440min to carry out slow cooling crystal growth.
[0039] Step 5: Naturally cool the high-temperature box-type muffle furnace to 25°C to obtain n-type Bi2Te that can be used for thermoelectric refrigeration. 2.7 Se 0.3 Cu 0.005 Crystalline materials.
[0040] Example 5
[0041] This embodiment discloses a Cu-doped Bi₂Te 2.7 Se 0.3 Crystal materials (Bi2Te) 2.7 Se 0.3 Cu x A method for preparing (x=0.01), the method comprising the following steps: Step 1: Use high-purity Bi, Te, Se and Cu particles as initial raw materials, and mix them according to the molar ratio of Bi:Te:Se:Cu=2:2.7:0.3:0.01 to obtain mixed raw materials.
[0042] Step 2: Place the mixed raw materials into a quartz tube and perform a vacuum treatment, with a vacuum degree of less than 1×10⁻⁶. - 3 Pa; The quartz tube is a quartz tube with a pointed bottom cone shape, and its wall thickness is not less than 1 mm. The angle θ of the bottom cone of the quartz tube is in the range of θ / 2=25°.
[0043] Step 3: First, raise the temperature of the high-temperature box-type muffle furnace to 800℃ at a rate of 60~70℃ / h, and maintain this temperature for 740 minutes to carry out the high-temperature melting synthesis reaction.
[0044] Step 4: After the high-temperature melting synthesis reaction, the temperature of the high-temperature box-type muffle furnace is reduced to 550℃ at a cooling rate of 1.5~2℃ / h, and this temperature is maintained for 1440min to carry out slow cooling crystal growth.
[0045] Example 6
[0046] This embodiment discloses a Cu-doped Bi₂Te 2.7 Se 0.3 Crystal materials (Bi2Te) 2.7 Se 0.3 Cu x A method for preparing (x=0.010), the method comprising the following steps: Step 1: Use high-purity Bi, Te, Se and Cu particles as initial raw materials, and mix them according to the molar ratio of Bi:Te:Se:Cu=2:2.7:0.3:0.01 to obtain mixed raw materials.
[0047] Step 2: Place the mixed raw materials into a quartz tube and perform a vacuum treatment, with a vacuum degree of less than 1×10⁻⁶. - 3 Pa; The quartz tube is a quartz tube with a pointed bottom cone shape, and its wall thickness is not less than 1 mm. The angle θ of the bottom cone of the quartz tube is in the range of θ / 2=25°.
[0048] Step 3: First, raise the temperature of the high-temperature box-type muffle furnace to 800℃ at a rate of 60~70℃ / h, and maintain this temperature for 740 minutes to carry out the high-temperature melting synthesis reaction.
[0049] Step 4: After the high-temperature melting synthesis reaction, the temperature of the high-temperature box-type muffle furnace is reduced to 550℃ at a cooling rate of 1.5~2℃ / h, and this temperature is maintained for 1440min to carry out slow cooling crystal growth.
[0050] Step 5: Naturally cool the high-temperature box-type muffle furnace to 20°C to obtain n-type Bi₂Te that can be used for thermoelectric refrigeration. 2.7 Se 0.3 Cu 0.01 Crystalline materials.
[0051] II. Preparation of Ag-doped samples Example 7
[0052] This embodiment discloses an Ag-doped Bi₂Te 2.7 Se 0.3 Crystal materials (Bi2Te) 2.7 Se 0.3 Ag x A method for preparing (x=0.005), the method comprising the following steps: Step 1: Use high-purity Bi, Te, Se and Ag particles as initial raw materials, and mix them according to the molar ratio of Bi:Te:Se:Ag=2:2.7:0.3:0.005 to obtain mixed raw materials.
[0053] Step 2: Place the mixed raw materials into a quartz tube and perform a vacuum treatment, with a vacuum degree of less than 1×10⁻⁶. - 3 Pa; The quartz tube is a quartz tube with a pointed bottom cone shape, and its wall thickness is not less than 1 mm. The angle θ of the bottom cone of the quartz tube is in the range of θ / 2=25°.
[0054] Step 3: First, raise the temperature of the high-temperature box-type muffle furnace to 800℃ at a rate of 60~70℃ / h, and maintain this temperature for 740 minutes to carry out the high-temperature melting synthesis reaction.
[0055] Step 4: After the high-temperature melting synthesis reaction, the temperature of the high-temperature box-type muffle furnace is reduced to 550℃ at a cooling rate of 1.5~2℃ / h, and this temperature is maintained for 1440min to carry out slow cooling crystal growth.
[0056] Step 5: Naturally cool the high-temperature box-type muffle furnace to 20°C to obtain n-type Bi₂Te that can be used for thermoelectric refrigeration. 2.7 Se 0.3 Ag 0.005 Crystalline materials.
[0057] Example 8
[0058] This embodiment discloses an Ag-doped Bi₂Te 2.7 Se 0.3 Crystal materials (Bi2Te) 2.7 Se 0.3 Ag x A method for preparing (x=0.01), the method comprising the following steps: Step 1: Use high-purity Bi, Te, Se and Ag particles as initial raw materials, and mix them according to the molar ratio of Bi:Te:Se:Ag=2:2.7:0.3:0.01 to obtain mixed raw materials.
[0059] Step 2: Place the mixed raw materials into a quartz tube and perform a vacuum treatment, with a vacuum degree of less than 1×10⁻⁶. - 3 Pa; The quartz tube is a quartz tube with a pointed bottom cone shape, and its wall thickness is not less than 1 mm. The angle θ of the bottom cone of the quartz tube is in the range of θ / 2=25°.
[0060] Step 3: First, raise the temperature of the high-temperature box-type muffle furnace to 800℃ at a rate of 60~70℃ / h, and maintain this temperature for 740 minutes to carry out the high-temperature melting synthesis reaction.
[0061] Step 4: After the high-temperature melting synthesis reaction, the temperature of the high-temperature box-type muffle furnace is reduced to 550℃ at a cooling rate of 1.5~2℃ / h, and this temperature is maintained for 1440min to carry out slow cooling crystal growth.
[0062] Step 5: Naturally cool the high-temperature box-type muffle furnace to 20°C to obtain n-type Bi₂Te that can be used for thermoelectric refrigeration. 2.7 Se 0.3 Ag 0.01 Crystalline materials.
[0063] Comparative Example 1 This comparative example discloses a Bi2Te 2.7 Se 0.3 Crystal materials (Bi2Te) 2.7 Se0.3 A method for preparing ), the method comprising the following steps: Step 1: Use high-purity Bi, Te and Se as initial raw materials, and mix them according to the molar ratio of Bi:Te:Se=2:2.7:0.3 to obtain mixed raw materials.
[0064] Step 2: Place the mixed raw materials into a quartz tube and perform a vacuum treatment, with a vacuum degree of less than 1×10⁻⁶. - 3 Pa; The quartz tube is a quartz tube with a pointed bottom cone shape, and its wall thickness is not less than 1 mm. The angle θ of the bottom cone of the quartz tube is in the range of θ / 2=25°.
[0065] Step 3: First, raise the temperature of the high-temperature box-type muffle furnace to 800℃ at a rate of 65℃ / h, and maintain this temperature for 740 minutes to carry out the high-temperature melting synthesis reaction.
[0066] Step 4: After the high-temperature melting synthesis reaction, the temperature of the high-temperature box-type muffle furnace is reduced to 550℃ at a cooling rate of 1.8℃ / h, and this temperature is maintained for 1440min for slow cooling crystal growth.
[0067] Step 5: Naturally cool the temperature of the high-temperature box-type muffle furnace to 20°C to obtain n-type Bi2Te. 2.7 Se 0.3 Crystalline materials.
[0068] Comparative Example 2 This comparative example discloses a Cu-doped Bi₂Te 2.7 Se 0.3 Crystal materials (Bi2Te) 2.7 Se 0.3 Cu x A method for preparing (x=0.015), the method comprising the following steps: Step 1: Use high-purity Bi, Te, Se and Cu particles as initial raw materials, and mix them according to the molar ratio of Bi:Te:Se:Cu=2:2.7:0.3:0.015 to obtain mixed raw materials.
[0069] Step 2: Place the mixed raw materials into a quartz tube and perform a vacuum treatment, with a vacuum degree of less than 1×10⁻⁶. - 3 Pa; The quartz tube is a quartz tube with a pointed bottom cone shape, and its wall thickness is not less than 1 mm. The angle θ of the bottom cone of the quartz tube is in the range of θ / 2=25°.
[0070] Step 3: First, raise the temperature of the high-temperature box-type muffle furnace to 800℃ at a rate of 60~70℃ / h, and maintain this temperature for 740 minutes to carry out the high-temperature melting synthesis reaction.
[0071] Step 4: After the high-temperature melting synthesis reaction, the temperature of the high-temperature box-type muffle furnace is reduced to 550℃ at a cooling rate of 1.5~2℃ / h, and this temperature is maintained for 1440min to carry out slow cooling crystal growth.
[0072] Step 5: Naturally cool the high-temperature box-type muffle furnace to 20°C to obtain n-type Bi2Te. 2.7 Se 0.3 Cu 0.015 Crystalline materials.
[0073] Comparative Example 3 This comparative example discloses a Cu-doped Bi₂Te 2.7 Se 0.3 Crystal materials (Bi2Te) 2.7 Se 0.3 Cu x A method for preparing (x=0.0175), the method comprising the following steps: Step 1: Use high-purity Bi, Te, Se and Cu particles as initial raw materials, and mix them according to the molar ratio of Bi:Te:Se:Cu=2:2.7:0.3:0.0175 to obtain mixed raw materials.
[0074] Step 2: Place the mixed raw materials into a quartz tube and perform a vacuum treatment, with a vacuum degree of less than 1×10⁻⁶. - 3 Pa; The quartz tube is a quartz tube with a pointed bottom cone shape, and its wall thickness is not less than 1 mm. The angle θ of the bottom cone of the quartz tube is in the range of θ / 2=25°.
[0075] Step 3: First, raise the temperature of the high-temperature box-type muffle furnace to 800℃ at a rate of 60~70℃ / h, and maintain this temperature for 740 minutes to carry out the high-temperature melting synthesis reaction.
[0076] Step 4: After the high-temperature melting synthesis reaction, the temperature of the high-temperature box-type muffle furnace is reduced to 550℃ at a cooling rate of 1.5~2℃ / h, and this temperature is maintained for 1440min to carry out slow cooling crystal growth.
[0077] Step 5: Naturally cool the high-temperature box-type muffle furnace to 20°C to obtain n-type Bi2Te. 2.7 Se 0.3 Cu 0.0175 Crystalline materials.
[0078] Comparative Example 4 This comparative example discloses a Cu-doped Bi₂Te 2.7 Se 0.3 Crystal materials (Bi2Te) 2.7Se 0.3 Cu x A method for preparing (x=0.02), the method comprising the following steps: Step 1: Use high-purity Bi, Te, Se and Cu particles as initial raw materials, and mix them according to the molar ratio of Bi:Te:Se:Cu=2:2.7:0.3:0.02 to obtain mixed raw materials.
[0079] Step 2: Place the mixed raw materials into a quartz tube and perform a vacuum treatment, with a vacuum degree of less than 1×10⁻⁶. - 3 Pa; The quartz tube is a quartz tube with a pointed bottom cone shape, and its wall thickness is not less than 1 mm. The angle θ of the bottom cone of the quartz tube is in the range of θ / 2=25°.
[0080] Step 3: First, raise the temperature of the high-temperature box-type muffle furnace to 800℃ at a rate of 60~70℃ / h, and maintain this temperature for 740 minutes to carry out the high-temperature melting synthesis reaction.
[0081] Step 4: After the high-temperature melting synthesis reaction, the temperature of the high-temperature box-type muffle furnace is reduced to 550℃ at a cooling rate of 1.5~2℃ / h, and this temperature is maintained for 1440min to carry out slow cooling crystal growth.
[0082] Step 5: Naturally cool the high-temperature box-type muffle furnace to 20°C to obtain n-type Bi2Te. 2.7 Se 0.3 Cu 0.02 Crystalline materials.
[0083] To further illustrate the group IB element doped n-type Bi₂Te of the present invention 2.7 Se 0.3 The performance advantages of crystal materials compared to existing technologies are highlighted by selecting n-type Bi₂Te from published literature. 2.7 Se 0.3 The thermoelectric materials used are cited as comparative examples in the literature. The preparation methods and thermoelectric performance data of Comparative Examples 5-7 are derived from publicly available literature. The room temperature power factor and room temperature ZT values are either reported values or obtained by reading and converting data from literature charts at approximately 300 K. These values are used solely for performance comparison with the embodiments of this invention.
[0084] Comparative examples: 5 books. The comparative examples are from the literature Yan X, Poudel B, Ma Y, Liu WS, Joshi G, Wang H, Lan Y, Wang D, Chen G, Ren ZF. Experimental studies on anisotropic thermoelectric properties and structures of n-type Bi2Te. 2.7 Se 0.3 Nano Letters, 2010, 10(9): 3373-3378. DOI: 10.1021 / nl101156v. The report describes an n-type Bi₂Te₂.₇Se₀.₃ thermoelectric material, sintered using SPS hot pressing of undoped Bi₂Te₂. 2.7 Se 0.3 Crystal materials (Bi2Te) 2.7 Se 0.3 A method for hot-pressing undoped Bi2Te using SPS (Silicon-Pulse-Screening) was proposed. 2.7 Se 0.3 Crystal materials (Bi2Te) 2.7 Se 0.3 The method includes the following steps: Step 1: Use high-purity Bi, Te, and Se particles as initial raw materials, and mix them according to the molar ratio of Bi:Te:Se = 2:2.7:0.3 to obtain mixed raw materials.
[0085] Step 2: Load the mixed raw materials into a stainless steel ball mill jar, add stainless steel balls, and perform high-energy ball milling under argon protection until the powder particle size reaches 20-50nm, to obtain alloyed nano powder.
[0086] Step 3: Load the ball-milled powder into a graphite mold with an inner diameter of 19.05 mm and place it into a DC hot press furnace.
[0087] Step 4: Hot pressing sintering under vacuum or protective atmosphere: hot pressing temperature is 450°C, pressure is 60MPa, and the temperature and pressure are held for 30 minutes.
[0088] Step 5: Cool the sample to room temperature in the furnace to obtain a cylindrical block with a diameter of 19.05 mm and a thickness of about 22.7 mm. The grains are randomly oriented, which is the hot-pressed sintered sample.
[0089] Comparative Example 6 This comparative example is from the literature Lee E, Kim JI, Choi SM, Lim YS, Seo WS, Kim JY, Lee K H. Thermoelectric transport properties of Cu nanoprecipitates embedded Bi₂Te 2.7 Se 0.3 Journal of Nanomaterials, 2015, 2015: 820893. DOI: 10.1155 / 2015 / 820893. Reported Cu nanoparticles embedded in Bi₂Te 2.7 Se 0.3 Nanocomposite bulk materials. The literature describes the preparation of Bi₂Te using lithiation and water exfoliation methods. 2.7 Se 0.3 A colloidal suspension of nanosheets was then prepared using CuCl2 as the copper source and hydrazine hydrate as the reducing agent, and exfoliated Bi2Te 2.7 Se 0.3 Cu nanoparticles were deposited in situ on the surface of nanosheets and then Cu-Bi2Te was prepared by SPS sintering. 2.7 Se 0.3 Nanocomposite bulk material. The preparation method includes the following steps: Step 1: Using high-purity Bi, Te, and Se as raw materials, mix them in a molar ratio of Bi:Te:Se = 2:2.7:0.3 to obtain a mixed raw material. Bi₂Te is then prepared first through a lithiation reaction and a water stripping method. 2.7 Se 0.3 Colloidal suspension of nanosheets.
[0090] Step 2: Take the Bi2Te obtained in Step 1 2.7 Se 0.3 The colloidal suspension of nanosheets was mixed with an aqueous CuCl2 solution, and 60.0 mL of hydrazine hydrate was added. The mixture was refluxed at 120°C for 180 minutes to allow Cu nanoparticles to precipitate uniformly on Bi2Te. 2.7 Se 0.3 Nanosheet surface.
[0091] Step 3: After the reaction is complete, the mixture is repeatedly washed, centrifuged, and dried under vacuum to obtain Cu nanoparticles and Bi2Te. 2.7 Se 0.3 Composite powder of nanosheets.
[0092] Step 4: Load the composite powder into a graphite mold and place it in a spark plasma sintering (SPS) furnace for sintering under vacuum conditions: sintering temperature is 420°C, pressure is 30MPa, and the temperature and pressure are maintained for 2 minutes.
[0093] Step 5: Cool to room temperature in the furnace to obtain a disc-shaped block with a diameter of 10 mm and a thickness of 13 mm, namely Bi2Te. 2.7 Se 0.3 Cu 0.01 Nanocomposite bulk materials.
[0094] Comparative examples: 7 books. The comparative examples are from the literature Lee KH, Choi SM, Kim SI, Roh JW, Yang DJ, Shin WH, Park HJ, Lee K, Hwang S, Lee JH, Mun H, Kim SW. Doping effects on the thermoelectric properties of Cu-intercalated Bi₂Te 2.7 Se 0.3 Current Applied Physics, 2015, 15(3): 190-193. DOI: 10.1016 / j.cap.2014.12.006. Reported Cu intercalated n-type Bi₂Te 2.7 Se 0.3 Thermoelectric materials. Bi2Te prepared by SPS hot pressing sintering. 2.7 Se 0.3 Crystal materials (Bi2Te) 2.7 Se 0.3 The method includes the following steps: Step 1: Use high-purity Bi, Te, and Se particles as initial raw materials, and mix them according to the molar ratio of Bi:Te:Se = 2:2.7:0.3 to obtain a mixed raw material; Step 2: Load the mixed raw materials into a stainless steel ball mill jar, add stainless steel balls, and perform high-energy ball milling under argon protection until the powder particle size reaches 20-50 nm to obtain alloyed nanoparticles.
[0095] Step 3: Load the ball-milled alloyed nanoparticles into a graphite mold with an inner diameter of 10 mm and place it into a DC hot press furnace.
[0096] Step 4: Hot pressing sintering under vacuum or protective atmosphere: hot pressing temperature is 420°C, pressure is 30MPa, and the temperature and pressure are held for 2 minutes.
[0097] Step 5: Cool the sample to room temperature in the furnace to obtain a disc-shaped block with a diameter of 10 mm and a thickness of 13 mm, which is the hot-pressed sintered sample.
[0098] The Bi2Te3 crystal material doped with Group IB elements obtained in Examples 1-8 (Bi2Te 2.7 Se 0.3 M x The crystal materials prepared in Examples 1-7 and Comparative Examples 1-7 were cut into regular cubes using a cutting machine, and the surfaces were polished with sandpaper before thermoelectric performance testing was performed. The thermoelectric performance included conductivity (σ) and Seebeck coefficient (α). The room temperature power factor and room temperature ZT value were then obtained. The specific data are shown in Table 1.
[0099] Table 1. Data on room temperature power factor and room temperature ZT value of the crystal materials prepared in Examples 1-8 and Comparative Examples 1-7.
[0100] As can be seen from the above embodiments and comparative examples, the N-type Bi2Te provided by the present invention... 2.7 Se 0.3 M x The crystal exhibits excellent thermoelectric transport properties and high performance repeatability at room temperature.
[0101] Because the atomic layer of Bi2Te3 is Te (1) -Bi-Te (2) -Bi-Te (1) Repeated arrangement in the same way, Te (1) -Te (1) The Bi-Te bonds are bonded by van der Waals bonds, while the Bi-Te bonds are relatively strong ionic-covalent mixed bonds. Due to the relatively small van der Waals bond energy, Te... (1) -Te (1) Cleavage fractures easily occur between the atomic layers, resulting in significant anisotropy in the Bi2Te3 crystal structure and transport properties. The electrical conductivity within the basal plane of n-type Bi2Te3 is six times that of the van der Waals interstitial (along the c-axis), and the lattice thermal conductivity along the basal plane is almost twice that in the perpendicular direction. Because the anisotropy of electrical conductivity exceeds that of thermal conductivity, single crystals and oriented polycrystalline materials exhibit higher ZT values within the ab plane. Therefore, when conducting thermoelectric performance tests, the crystal material needs to be cut into regular cubes using a cutting machine. The element should be cut parallel to the cleavage plane, and its surface should be polished with sandpaper before the thermoelectric performance tests are performed. The thermoelectric performance includes electrical conductivity (σ) and Seebeck coefficient (α). Based on the data measured in Table 1, the power factor ( To evaluate the electrical properties of materials, Figure 1 , Figure 2 and Figure 3The Bi2Te3 crystal materials doped with Group IB elements obtained in Examples 1-8 are respectively (Bi2Te 2.7 Se 0.3 M x The electrical conductivity, Seebeck coefficient, and power factor of the crystalline materials prepared in Examples 1-7 were compared. In addition, the thermoelectric properties included the thermal diffusivity (D) and specific heat capacity (C). p Based on the measured data and the material's density (ρ), the total thermal conductivity (...) can be used to determine the thermal conductivity. The thermal properties of a material are represented by ( ). Figure 4 The Bi2Te3 crystal material doped with Group IB elements obtained in Examples 1-8 (Bi2Te 2.7 Se 0.3 M x The total thermal conductivity of the crystalline materials prepared in Comparative Examples 1-7 is higher than that of the crystalline materials prepared in Comparative Examples 1-7. Figure 5 The Bi2Te3 crystal material doped with Group IB elements obtained in Examples 1-8 (Bi2Te 2.7 Se 0.3 M x The ZT values of the crystal materials prepared in Comparative Examples 1-7 are ( ) and ( ) ).
[0102] This invention optimizes the near-room temperature thermoelectric properties of n-type Bi2Te3 by doping Bi2Te3 crystals with group IB elements (Cu, Ag), ultimately achieving a thermoelectric ZT value of ≥1.09 for n-type Bi2Te3, which is of great significance for the future development and application of thermoelectric refrigeration materials.
[0103] Furthermore, the n-type Bi₂Te prepared in Example 6, which is doped with a Group IB element, was used... 2.7 Se 0.3 Cu 0.01 Crystal materials are cut into n-type thermoelectric arms and combined with p-type bismuth telluride-based thermoelectric materials. 0.48 Sb 1.52 Te 3.06 Thermoelectric arms, electrode plates, and insulating ceramic substrates were assembled into seven pairs of full-size near-room-temperature thermoelectric cooling modules. The steady-state cooling performance of these seven pairs of thermoelectric cooling modules was then tested. During the test, a constant-temperature hot stage was used to raise the hot-end temperature T... h The operating currents were set to 303K, 323K, and 343K. Different operating currents were applied to the module via a DC power supply. After the module reached steady state, the hot junction temperature T was recorded. h and cold end temperature T c And according to ΔT=T h -T c Calculate the refrigeration temperature difference, and then plot as follows: Figure 6 and Figure 7 The refrigeration temperature difference-current curve. (From...) Figure 6It can be seen that as the operating current increases, the module's cooling temperature difference gradually increases, and tends to stabilize at higher currents; at T h At 303K, 323K and 343K, the module achieved maximum cooling temperature differences of approximately 64.8K, 73.87K and 81.95K, respectively.
[0104] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention in any way. Any simple modifications, alterations, and equivalent changes made to the above embodiments based on the inventive essence shall still fall within the protection scope of the present invention.
Claims
1. A group IB element-doped n-type bismuth telluride thermoelectric material, characterized in that, The n-type bismuth telluride thermoelectric material doped with Group IB elements is a crystalline material with the general chemical formula Bi₂Te. 2.7 Se 0.3 M x , where M represents a group IB element, selected from Cu or Ag; When M is Cu, the value of x is: 0.0025≤x≤0.010; When M is Ag, the value of x is: 0.005≤x≤0.
01.
2. A method for preparing the n-type bismuth telluride thermoelectric material doped with Group IB elements as described in claim 1, characterized in that, The method is as follows: Step 1: Use Bi, Te, Se and M with a purity of not less than 99.5% as raw materials, and mix them in a molar ratio of Bi, Te, Se and M of 2:2.7:0.3:x to obtain mixed raw materials; Step 2: Place the mixed raw materials obtained in Step 1 into a quartz tube and perform high-temperature melting to synthesize a compound; Step 3: The compound synthesized in Step 2 is subjected to slow cooling crystal growth to obtain n-type bismuth telluride thermoelectric material doped with group IB elements.
3. The method according to claim 2, characterized in that, In step two, the mixed raw materials are placed in a quartz tube and subjected to vacuum treatment, with a vacuum degree of less than 1×10⁻⁶. -3 Pa, the vacuum-sealed quartz tube is vertically placed in a high-temperature box-type muffle furnace for high-temperature melting and synthesis reaction; the quartz tube is a bottom-conical quartz tube with a wall thickness of not less than 1 mm, and the angle θ of the bottom cone of the quartz tube is in the range of 15°≤θ / 2≤25°.
4. The method according to claim 3, characterized in that, The high-temperature melting synthesis reaction described in step two is as follows: First, the quartz tube containing the mixed raw materials is placed in a high-temperature box-type muffle furnace, and the high-temperature box-type muffle furnace is heated to 800℃ at a rate of 60~70℃ / h and held at that temperature for 700~750min.
5. The method according to claim 4, characterized in that, The cooling growth described in step three specifically involves: The temperature of the high-temperature box-type muffle furnace was reduced to 520-570℃ at a rate of 1.5-2℃ / h and held for 1400-1500 min for slow cooling crystal growth; then the temperature was naturally cooled to 20-30℃ to obtain n-type bismuth telluride thermoelectric material doped with group IB elements.
6. A thermoelectric cooling device, characterized in that, The thermoelectric cooling device includes the n-type bismuth telluride-based thermoelectric material doped with group IB elements as described in claim 1.
7. The application according to claim 6, characterized in that, The n-type bismuth telluride-based thermoelectric material doped with group IB elements and the p-type bismuth telluride-based thermoelectric material Bi 0.48 Sb 1.52 Te 3.06 When used together, they form seven pairs of near-room temperature full-size thermoelectric refrigeration modules.